History of Land-Use Policies and Designation of Mount Halimun-Salak National Park - Gama Galudra; M Sirait; N Ramdhaniaty; F Soenarto; B Nurzaman (Jurnal Manajemen Hutan Tropika, 2005)
he extension and designation of Gunung Halimun-Salak National Park has caused land conflict issue widely.  Many local communities have used this national park land for their agriculture crops and dwelling.  Through the historical perspective, it was found that this land conflict was due to ongoing change of land use policies. The government, from the Dutch Colonial to Japan occupation, imposed different land use policy to the Halimun-Salak land.  These changing policies have caused many local communities living inside the current designated state forestland.  Regretabbly, the current government did not solve this land conflict, but rather offered uncertainty by permitting and charging the local communities who cultivate inside the state forestland.  Undoubtedly, this uncertainty has caused problems in the future to the national park.  It was thought that border arrangement will solve this land conflict as it has been proven that changing policies have change the land-use in Halimun-Salak area.